Pengaruh Model Kooperatif Teams Games Tournament (TGT) Berbasis Media Kartu Soal pada Materi Gelombang Bunyi terhadap Pemahaman Konsep Fisika Siswa - Lika Adeliana Putri; Sutri Novika; Rita Destini; Jafri Haryadi (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aimed to examine the effect of the Teams Game Tournament (TGT) learning model assisted by Question Cards on senior high school students’ conceptual understanding of sound wave material. The research employed a quantitative approach with a quasi-experimental design using the nonequivalent control group design. The subjects were eleventh-grade students of SMAN 2 Lubuk Pakam, with class XI-C as the experimental group (36 students) and class XI-A as the control group (34 students). The research instruments consisted of pretest and posttest questions as well as observation sheets. The results showed a significant improvement in students’ conceptual understanding after the implementation of the TGT model assisted by Question Cards. Based on the hypothesis testing using an independent samples t-test, the posttest significance value was 0.000 < 0.05, indicating a significant difference between the experimental and control groups. The N-Gain analysis revealed that the experimental group achieved an average N-gain score of 0.65 (moderate to high category), while the control group obtained 0.31 (low to moderate category). These findings indicate that the TGT model assisted by Question Cards is more effective in improving conceptual understanding than the lecture method. In conclusion, the use of the TGT model assisted by Question Cards has a positive and significant effect on enhancing students’ understanding of physics concepts. This model is able to create an active, enjoyable, and competitive learning environment while simultaneously increasing students’ participation and self-confidence in understanding the material.